A naturalized diploid Fragaria sp. (Rosaceae) found in southern Chile as revealed by morphological, ploidy and cytogenetic analyses - Figueroa, Carlos R.; Quilodrán, Manuel; Peñailillo, Patricio; Baeza, Carlos M.; Arrey-Salas, Oscar (Phytotaxa, 2023)
Fragaria genus has a worldwide distribution and different ploidy levels. The only wild Fragaria species described in Chile is the octoploid Fragaria chiloensis. In a group of Fragaria accessions from southern Chile including Fragaria chiloensis subsp. chiloensis f. patagonica individuals, an accession named Fragaria-MEN, caught our attention because it shows notable phenotypic differences compared to the rest of the accessions. Fragaria-MEN was collected near the Menetue hot springs (Araucania Region, Chile) and differs from the other F. chiloensis plants mainly in leaf morphology. Due to these differences, we carried out a full morphology description of Fragaria-MEN individuals and then a characterization of the chromosomes and genome size to verify the ploidy level. Morphological analysis reveals close vegetative and reproductive characteristics shared with the non-native diploid Fragaria vesca ‘Hawaii’ species. We also observed a DNA amount according to the diploidy (2n = 2× = 14) revealed by cytological analysis of chromosomes. We propose Fragaria-MEN as F. vesca population that should have been introduced and now is naturalized in the Araucania Region of Chile.